Macrophage Polarization: Convergence Point Targeted by Mycobacterium Tuberculosis and HIV - Lugo-Villarino, Geanncarlo; Verollet, Christel; Maridonneau-Parini, Isabelle; Neyrolles, Olivier (Frontiers in Immunology, 2011)
In the arms race of host-microbe co-evolution, macrophages (Mφs) have been endowed with strategies to neutralize pathogenic challenge while preserving host integrity. During steady-states conditions, Mφs perform multiple house-keeping functions governed by their differentiation state, tissue distribution and signals from the microenvironment. In response to pathogenic challenge and host mediators, however, Mφs undergo different programs of activation rendering them either pro-inflammatory and microbicidal (M1), or immunosuppressants and tissue repairers (M2). An excessive or prolonged polarization of either program may be detrimental to the host due to potential tissue injury or contribution to pathogenesis. Conversely, intracellular microbes that cause chronic diseases such as TB (tuberculosis) and AIDS (acquired immunodeficiency syndrome) exemplify strategies for survival in the host. Indeed, both Mtb (M. tuberculosis) and HIV-1 (human immunodeficiency virus) are successful intracellular microbes that thrive in Mφs. Given these microbes not only co-circulate throughout the developing world but each has contributed to prevalence and mortality caused by the other, substantial insights into microbe physiology and host defenses then rest in the attempt to fully understand their influence on Mφ polarization. This review addresses the role of Mφ polarization in the immune response to, and pathogenesis of, Mtb and HIV.